Influenza A Virus Infection in Cats and Dogs: A Literature Review in the Light of the “One Health” Concept - Borland, Stéphanie; Gracieux, Patrice; Jones, Matthew; Mallet, François; Yugueros-Marcos, Javier (Frontiers in Public Health, 2020)
Influenza A viruses are amongst the most challenging viruses that threaten both human and animal health. Constantly evolving and crossing species barrier, the emergence of novel zoonotic pathogens is one of the greatest challenges to global health security. During the last decade, considerable attention has been paid to influenza virus infections in dogs, as two canine H3N8 and H3N2 subtypes caused several outbreaks through the United States and Southern Asia, becoming endemic. Cats, even though less documented in the literature, still appear to be susceptible to many avian influenza infections. While influenza epidemics pose a threat to canine and feline health, the risks to humans are largely unknown. Here, we review most recent knowledge of the epidemiology of influenza A viruses in dogs and cats, existing evidences for the abilities of these species to host, sustain intraspecific transmission, and generate novel flu A lineages through genomic reassortment. Such enhanced understanding suggests a need to reinforce surveillance of the role played by companion animals-human interface, in light of the “One Health” concept and the potential emergence of novel zoonotic viruses.